DESCRIPTION OF MATHEMATICS LEARNING WITH CHARACTER AT SMPN 5 MANDAI IN MAROS DISTRICT - Juharia, Nasri (Universitas Negeri Makassar, 2019)
The study aims at describing teachers’ activities based on the aspects of preparation, implementation, and evaluation of learning in Mathematics learning process which affected on students’ character building at SMPN 5 Mandai. The type of this study was descriptive research with qualitative approach. The research subjects were 2 Mathematics teachers at SMPN 5 Mandai who applied 2013 curriculum and teachers who applied character education in learning process. Data collecting method of the study were interview, observation, and documentation. The study employed triangulation method by comparing the data obtained through documentation with observation, and observation with interview. The results of the study reveal that (1) teachers’ activities based on the aspects of preparation in Mathematics learning process which affected on the students’ character building can be seen from syllabus arrangement and lesson plan of teachers, (2) teachers’ activities based on the implementation aspect in Mathematics learning process which affected on students’ character building are the teachers applied character education started from opening activity, main activity, and closing activity, (3) teachers’ activities based on the evaluation aspect in Mathematics learning process which affected on students’ character building are through competence of students’ attitude aspect, knowledge aspect such as giving daily examination, and skills. Students’ development can be acknowledged by teachers and parents as well as by students’ themselves. The evaluation of Mathematics learning with character at SMPN 5 Mandai in Maros discrit has been conducted integrated with teaching and learning activity